Polyethylenimine-mediated controlled synthesis of Prussian blue-gold nanohybrids for biomedical applications - Pandey P.; Pandey G.; Narayan R. (My University, 2025)
We report on polyethylenimine (PEI)-mediated synthesis of Prussian blue nanoparticles (PBNPs) and gold nanoparticles (AuNPs); the formation of PBNP-AuNP nanohybrids with a remarkable change in Prussian blue character as a function of gold cation concentration was also considered. It was shown that PEI-protected polycrystalline PBNPs can be synthesized in an acidic medium from the precursor potassium ferricyanide [K3Fe(CN)6] at 60 °C. Since PEI also enables the controlled formation of gold nanoparticles (AuNPs) in the presence of formaldehyde under ambient conditions, nanohybrids of PBNPs and AuNPs were prepared. The formation of AuNPs was recorded over a wide range of PEI concentrations, which allowed control over polymeric cation capping of the AuNPs. PEI concentration-dependent enhancement/quenching of fluorescence/resonance Rayleigh scattering was useful for non-enzymatic detection of serum glucose levels. The resonance Rayleigh scattering intensity of PBNPs was several-fold higher than that of AuNPs and acted as a potent quencher of fluorescence. At an optimal concentration of PEI, AuNPs allowed an increase in the fluorescence signal as function of glucose concentration; the quenching ability of PB was demonstrated to be a function of the glucose concentration. This method is efficient for fast glucose sensing and offers a wider linear dynamic range, 0–10 mM, which is useful for non-enzymatic detection of serum glucose levels. © The Author(s) 2020.